Keroncong Performance Adaptation Strategies in the Context of Creative Industries (Case Study of the Congwayndut Group) (Universitas Negeri Semarang, 2022)
Keroncong performances in Indonesia are now increasingly difficult to find both in rural and urban areas. The demands that arise due to the demands of the performing arts industry make keroncong also have to adapt to follow the direction of the creative industry to survive, including the Congwayndut group as performers of the performing arts creative industry. This study aims to analyze the adaptation strategy of the Congwayndut group's keroncong performance in dealing with the performing arts creative industry. The type of research used is descriptive qualitative using data collection techniques of observation, interviews, and documentation. Data analysis methods used are data collection, data presentation, data reduction, and data verification. The results showed that the form of the Congwayndut group's keroncong performance adapted from theatrical performances and made a breakthrough by renewing the keroncong performance combined with wayang art. The adaptation strategy used by the Congwayndut group to survive is by shifting to digital platforms (shifting to digital), building relationships in creative containers (creative hub), and rediscovering potential and opportunities (reinventing the trend). This is intended so that in the future the keroncong performance can be well received by the community. In addition, the creative industry practices contained in the adaptation strategy used will be able to improve the welfare of the Congwayndut group's artists.